2014
DOI: 10.1016/j.vaccine.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and stimulation of the zebrafish (Danio rerio) innate immune system with LPS/dsRNA-loaded nanoliposomes

Abstract: Herein we report the use of immunostimulant-loaded nanoliposomes (called NLcliposomes) as a strategy to protect fish against bacterial and/or viral infections. This work entailed developing a method for in vivo tracking of the liposomes administered to adult zebrafish that enables evaluation of their in vivo dynamics and characterisation of their tissue distribution. The NLc liposomes, which co-encapsulate poly(I:C) and LPS, accumulate in immune tissues and in immunologically relevant cells such as macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…For example, Ruyra et al. () successfully encapsulated lipopolysaccharide (LPS) within a liposome to produce an efficacious immersion vaccine in zebrafish, Danio rerio , against a gram‐negative bacteria Pseudomonas aeruginosa . Ruyra et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ruyra et al. () successfully encapsulated lipopolysaccharide (LPS) within a liposome to produce an efficacious immersion vaccine in zebrafish, Danio rerio , against a gram‐negative bacteria Pseudomonas aeruginosa . Ruyra et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ruyra et al. () also determined that empty liposomes and unassociated LPS were not efficacious against the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Adult zebrafish (0.64 ± 0.17 g body weight) were transferred to an isolated system and acclimatized 1 day before each experiment. Pseudomonas aeruginosa (PAO1) was cultured and grown as previously described [33]. Two different cytokines, CCL4 and TNFα, were successfully produced in E. coli as IBs ( Figure 1A).…”
Section: In Vivo Immunization With Tnfα and Ccl4 Ibsmentioning
confidence: 99%
“…In addition, more recently, it has also become a model for those researchers working in fish immunology and vaccinology (Phelps and Neely, 2005;Boltana et al, 2013;Garcia-Valtanen et al, 2013Varela et al, 2014). We (Ruyra et al, 2014) and others have shown that zebrafish is an excellent model to study bioactive compounds prior to performing more laborious and expensive analysis in commercial species. Although zebrafish use is growing in many laboratories to replace the use of rodents or commercial fish species, there is a lack of wellcharacterised zebrafish in vitro models.…”
Section: Introductionmentioning
confidence: 99%